A High Power Interleaved Parallel Topology Full-Bridge LLC Converter for Off-Board Charger - Jianbin Chen (IEEE, 2021)
An interleaved parallel LLC converter is proposed as a DC/DC converter for a digital off-board charger in accordance with the high output power requirements of modern electric vehicle chargers. The proposed converter utilizes a hybrid control strategy of pulse frequency modulation (PFM) and pulse width modulation (PWM) that can greatly increase the adjustable output voltage range. As a result of these designs, a silky target voltage can be achieved. The proposed LLC converter has been rigorously analyzed and parametrically designed. To verify the design parameters of the proposed LLC converter, a laboratory prototype with an output voltage range of 40–110 V and a maximum output power of 20 kW was fabricated. The rated output voltage and rated output current are 80 V and 200 A, respectively, while its switching frequency range is 100–250 kHz and its resonant frequency is 153 kHz. This prototype exhibits incredible robustness and stability and achieves flexibility, stability, and sensitivity to automatically adapt to the target output voltage value.